Power and Solidarity in Muslim Eid and Christian Easter Sermons: A Sociolinguistic Study - Mahdi, Athraa' Ammar; Dawood, Mahmood A. (Al-Adab Journal, 2022)
The purpose of the present study is to demonstrate that sermon as a form of religious discourse, and that study is deals with Socio-linguistic angle. The problem is raised in this study, whether the most common lexical linguistic expressions of power and solidarity, presented by Brown and Gilman (1960), are existed in both languages (Arabic and English) of selected sermons, with specifying their rates of frequency occurrences. The current study aims at specifying the widely used of lexical linguistic expressions which indicated the power and the solidarity in these selected sermons [Easter Hope Sermon and بشائر الامة وامالها (Omens and hopes of the nation)]. In order to achieve this aim, the following hypotheses must be conducted:1- Every language has particular language markers of lexical expressions to reflect power and solidarity. The power of lexical linguistic expressions is the most frequency of occurrences in Arabic selected sermon, while the Solidarity of the lexical linguistic expressions is the most frequency of occurrences in English selected sermon.2- The lexical linguistic expressions are used to maximize or minimize the distance between the addresser and the addressee.